Analysis of the problem preparedness activities in psychological and educational literature (Pedagogy of Higher and Secondary Education, 2014)
Shulga A. V. Analysis of the problem preparedness activities in psychological and educational literature.The paper reveals the concept of readiness as an important component of psychological human activities that count for any business and its effective completion. Along with the concept of readiness is also used as a concept preparedness and attitudes, but these concepts are not identical. Approaches to the definition of psychological readiness and its forms.
Keywords: psychological readiness; preparedness; attitudes; willingness to act; a willingness to work